2015
DOI: 10.1177/003335491513000207
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Monitoring in Men Prescribed Testosterone Therapy in the U.S., 2001–2010

Abstract: Objectives. The Endocrine Society recommends testosterone therapy only in men with low serum testosterone levels, consistent symptoms of hypogonadism, and no signs of prostate cancer. We assessed screening and monitoring patterns in men receiving testosterone therapy in the U.S. Methods. We conducted a retrospective cohort study of 61,474 men aged ⩾40 years, and with data available in one of the nation's largest commercial insurance databases, who received at least one prescription for testosterone therapy fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 31 publications
1
32
0
Order By: Relevance
“…In a study of men in the United States and United Kingdom, only 14% of men in the United Kingdom and 10% of the men in the United States had more than one testosterone test within 180 days of receiving a prescription for testosterone (28). Another study from the United States showed a similar result, with only 18% of men receiving at least two testosterone tests in the 12 months prior to initiating treatment (29).…”
Section: Testosterone Therapy For Male Hypogonadismmentioning
confidence: 96%
See 2 more Smart Citations
“…In a study of men in the United States and United Kingdom, only 14% of men in the United Kingdom and 10% of the men in the United States had more than one testosterone test within 180 days of receiving a prescription for testosterone (28). Another study from the United States showed a similar result, with only 18% of men receiving at least two testosterone tests in the 12 months prior to initiating treatment (29).…”
Section: Testosterone Therapy For Male Hypogonadismmentioning
confidence: 96%
“…Although testing is required for the diagnosis of male hypogonadism, several studies show that men are commonly prescribed testosterone without any laboratory testing at all (29,31). Or, testosterone is prescribed to men with baseline testosterone levels that are normal or even high, with rates of such prescriptions ranging from 4 to 9% up to 20% (29,31).…”
Section: Testing Of and Prescriptions For Testosteronementioning
confidence: 99%
See 1 more Smart Citation
“…This challenge is not unique to Canada. 16,17 The stated purpose of the survey is to eventually develop a Canadian registry of hypogonadal men with a history PCa and receiving testosterone treatment. It is evident that only a countrywide registry would provide the power to address some of the pressing issues related to testosterone administration to men with PCa.…”
mentioning
confidence: 99%
“…2,3 Such stunning increases (which exclude pharmacy compounding and illicit nonprescription sources) are inexplicable in the absence of any proven new indications or well-controlled interventional trials over this time. 4 Interestingly, although the increased testosterone usage is reflected in data originating from health sector third parties, such as insurance 5,6 or governmental health scheme 7,8 databases, those sources substantially underestimate the magnitude of the increase. This dichotomy points to the fact that most unjustified testosterone prescribing occurs via doctors not subjected to third-party scrutiny such as through formulary and/or reimbursement restrictions in the veterans administration system 6 or in the health systems of a Canadian province 8 and Australia.…”
mentioning
confidence: 99%